2022
DOI: 10.1002/best.202200072
|View full text |Cite
|
Sign up to set email alerts
|

Frost‐Tausalz‐Widerstand von Mörtel: Einfluss der Expositionsbedingungen im jungen Alter

Abstract: Das Porensystem im Beton, bestehend aus Gel‐ und Kapillarporen, beeinflusst dessen Wasseraufnahmefähigkeit und so direkt auch den Frost‐Tausalz‐Widerstand. Unterschiedliche Expositionsbedingungen im jungen Alter des Betons haben dabei einen ausgeprägten Einfluss auf die Ausbildung des Porensystems. Um die Rolle der Vorkonditionierung auf das sich ausbildende Porengefüge und so den Frost‐Tausalz‐Widerstand von Beton zu klären, wurden Proben bei unterschiedlichen relativen Luftfeuchten vorkonditioniert und ansch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Consequently, the salt frost scaling resistance for simple systems can be predicted to some extent, as was recently shown Haynack et al [35] for OPC-based mortars without air entrainment.…”
Section: Capillary Porosity Vs Salt Frost Scaling Resistance With Por...mentioning
confidence: 64%
“…Consequently, the salt frost scaling resistance for simple systems can be predicted to some extent, as was recently shown Haynack et al [35] for OPC-based mortars without air entrainment.…”
Section: Capillary Porosity Vs Salt Frost Scaling Resistance With Por...mentioning
confidence: 64%
“…According to Thiel et al [34] frost suction mainly causes water transport from the test surface into deeper layers of the concrete while in the surface region, only a small increase in saturation is possible before the damage starts. Haynack et al [35] showed by 1H-NMR measurements that the amount of scaling during the CDF test (with deicing salts) depends on the preconditioning of the specimens. According to [35], two different factors have to be considered: the saturation degree at the beginning of the freeze-thaw exposure and the hydration degree depending on the preconditioning.…”
Section: Introductionmentioning
confidence: 99%
“…Haynack et al [35] showed by 1H-NMR measurements that the amount of scaling during the CDF test (with deicing salts) depends on the preconditioning of the specimens. According to [35], two different factors have to be considered: the saturation degree at the beginning of the freeze-thaw exposure and the hydration degree depending on the preconditioning.…”
Section: Introductionmentioning
confidence: 99%